Extraction and Characterization of Glucomannan from Porang (Amorphopallus oncophyllus) with Size Variations of Porang - Mella Nur Anissa; Sri Rahayoe; Eni Harmayani; Kamila Nikmatul Ulya (agriTECH, 2023)
Porang (Amorphophallus oncophyllus) is a tuber plant with high economic value as a raw material for making glucomannan. In this context, glucomannan possesses soluble properties, enabling the material to form a gel and contribute to thickening used in the food, pharmaceutical, and chemical industries. The extraction process uses porang harvested at the age of 3 years, with a size ranging from 10 to 20 cm. Even though the content is established, crucial information regarding the yield and different physical properties, such as viscosity, moisture content, and whiteness, remains unknown. Further analysis on glucomannan extraction should be performed with different age variations, before and after 3 years, namely 1 year, 2 years, and 4 years. Therefore, this study aimed to characterize and test the porang effects of various ages on the yield and physical properties of glucomannan, including viscosity, moisture content, and whiteness. The glucomannan extraction process included heating, filtering, 1:1 extraction, grinding, drying, flouring, and sieving. The results showed that the yield ranged from 49.33 - 69.33%, while the physical properties, including viscosity, moisture content, whiteness, and glucomannan content ranged from 31.556 - 39.556 m. Pas, 4.74 - 6.99%, 81.14 - 83.24%, and 95.13 - 97.57%, respectively. The variations in age of 1 year, 2 years, and 4 years affected yield, but the porang tubers had no effect on glucomannan content, and the quality of the flour on viscosity, moisture content, and whiteness. The variations with different ages met commercial standards, and the best variation was 1-year-old porang tubers with the highest yield of 65.33%. Concerning the physical properties, the highest viscosity, moisture content, whiteness, and glucomannan content was 39.556 m. Pas, 17%, 83.24% and 95.13%, respectively. Therefore, the plant could be harvested at 1 year old for extraction to meet export needs.